2018
DOI: 10.1177/0009922818790060
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Early Deaths Following Neonatal Male Circumcision in the United States, 2001 to 2010

Abstract: We sought to quantify early deaths following neonatal circumcision (same hospital admission) and to identify factors associated with such mortality. We performed a retrospective analysis of all infants who underwent circumcision in an inpatient hospital setting during the first 30 days of life from 2001 to 2010 using the National Inpatient Sample. Over 10 years, 200 early deaths were recorded among 9 833 110 subjects (1 death per 49 166 circumcisions). Note: this figure should not be interpreted as causal but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…While acknowledging that complication rates from routine circumcision are low, critics argue that the chances of these complications being mutilatory, infective, or haemorrhagic are high and potentially catastrophic. Critics further argue that death, gangrene, and total or partial amputation are known adverse outcomes (Fox and Thomson 2005;Earp et al 2018;Elhaik 2019).…”
Section: Risks Of Male Circumcisionmentioning
confidence: 99%
See 1 more Smart Citation
“…While acknowledging that complication rates from routine circumcision are low, critics argue that the chances of these complications being mutilatory, infective, or haemorrhagic are high and potentially catastrophic. Critics further argue that death, gangrene, and total or partial amputation are known adverse outcomes (Fox and Thomson 2005;Earp et al 2018;Elhaik 2019).…”
Section: Risks Of Male Circumcisionmentioning
confidence: 99%
“…Deaths have also been reported. In the United States, deaths following circumcision in clinical settings occur at a rate of approximately 1 for every 50,000 circumcisions (Earp et al 2018;Shahvisi and Earp 2019). This figure is disputed.…”
Section: Critique Of the Practicementioning
confidence: 99%
“…Infant MC‐related deaths are exceedingly rare, and occur mostly in nonmedical community circumcisions. Data from the US National Inpatient Sample found that during 2000‐2010, one death was recorded per 49 166 circumcisions during the first 30 days of life . The authors stressed that, “ this figure should not be interpreted as causal but correlational ” and “ may include both undercounting and overcounting .” Deaths were most common in neonates with significant comorbidities such as cardiac disease (OR 698), pulmonary circulatory disorders (OR 170), coagulopathy (OR 160), or fluid and electrolyte disorders (OR 68) (all P < .001).…”
Section: Physical Harmmentioning
confidence: 99%
“…MNC involves maternal separation and restraint to a board with removal of highly sensitive penile tissues, which may increase the risk of long-term adverse psychosexual sequelae [29][30][31][32]. Research suggests that procedures that are far milder than MNC, such as routine heel punctures, can have persistent negative effects with changes to immune, endocrine, and behavioral reactions to stressful events continuing into childhood or even adulthood [33,34] Deaths following MNC have been known for a long time as also acknowledged in the Talmud [35] to present time [36] with most deaths associated with excessive bleeding, infection, and less frequently with anesthesia accidents and cardiac arrest (reviewed in [37]). Recently, Earp et al analyzed data from a US inpatient database of nearly 10 million MNCs over 10 years.…”
Section: Introductionmentioning
confidence: 99%
“…The authors attributed an early death rate of 2/100,000 to MNC. The risk of early death (first 30 days) increased for infants circumcised in a teaching hospital and if comorbid conditions (e.g., cardiac diseases) are present [36]. This death rate should be considered an underestimate, provided the lack of systematic collection of mortality statistics associated with non-therapeutic circumcision in the US, which precludes, for instance, tracking deaths occurring in a hospital other than the hospital where circumcision took place.…”
Section: Introductionmentioning
confidence: 99%